Positioning infrastructure and technologies for low‐carbon urbanization. (30th October 2014) - Chester, Mikhail V.; Sperling, Josh; Stokes, Eleanor; Allenby, Braden; Kockelman, Kara; Kennedy, Christopher; Baker, Lawrence A.; Keirstead, James; Hendrickson, Chris T.
Abstract The expected urbanization of the planet in the coming century coupled with aging infrastructure in developed regions, increasing complexity of man‐made systems, and pressing climate change impacts have created opportunities for reassessing the role of infrastructure and technologies in cities and how they contribute to greenhouse gas (GHG) emissions. Modern urbanization is predicated on complex, increasingly coupled infrastructure systems, and energy use continues to be largely met from fossil fuels. Until energy infrastructures evolve away from carbon‐based fuels, GHG emissions are critically tied to the urbanization process. Further complicating the challenge of decoupling urban growth from GHG emissions are lock‐in effects and interdependencies. This paper synthesizes state‐of‐the‐art thinking for transportation, fuels, buildings, water, electricity, and waste systems and finds that GHG emissions assessments tend to view these systems as static and isolated from social and institutional systems. Despite significant understanding of methods and technologies for reducing infrastructure‐related GHG emissions, physical, institutional, and cultural constraints continue to work against us, pointing to knowledge gaps that must be addressed. This paper identifies three challenge themes to improve our understanding of the role of infrastructure and technologies in urbanization processes and position these increasingly complex systems for low‐carbon growth. The challenges emphasize how we can reimagine the role of infrastructure in the future and how people, institutions, and ecological systems interface with infrastructure.